Playing the game the history of Adidas - Karlsch, Rainer 1957-; Kleinschmidt, Christian 1961-; Lesczenski, Jörg 1966-; Sudrow, Anne 1970- (Siedler Verlag, 2018)
This history of Adidas, one of the world's most innovative global companies, looks beyond the trademark three stripes to show how the company grew and evolved over time. Founded in a small town in Bavaria, Germany, the Adidas brand has, for nearly a century, been outfitting international sports stars and pop culture icons such as David Beckham, Zin dine Zidane, and Run-DMC as well as everyday men, women, and children across the globe. The story of this evolution--illustrated with numerous historic photographs--is entwined with history, corporate trends, and the emergence of sports as a major factor in the world economy. Starting with the beginnings of the original Dassler brothers' company in the time of the Weimar Republic and National Socialism, this book reveals the first academically-based look at the history of the family and the Adidas company which was officially founded in 1949 after the brothers' separation. Using a worldwide range of sources, the authors also examine brand strategies and globalization since the 1960s. Since its beginnings, the name 'Adidas' has been shrouded in legend and, in this special look at the rise of a global company, readers will learn the true story behind the brand
Keywords: Adidas-Salomon AG.; adidas AG; Geschichte; Sporting goods industry -- Germany -- History; Footwear industry -- Germany -- History; Athletic shoes -- History; Adidas-Salomon AG. / (OCoLC)fst00762444; Germany / (OCoLC)fst01210272; History